A rare case of rapidly progressive Tracheobronchopathia Osteochondroplastica - Hulya Abali (Respiratory Medicine Case Reports, 2023)
Tracheobronchopathia Osteochondroplastica (TO) is a rare benign disorder that is seldom progressive. Here, we report a case diagnosed with TO in our hospital. Bronchoscopy revealed multiple cartilaginous and ossifying nodules that are diagnostic for TO. Nodules protruding into the airways were observed as widespread and extended by the repeat bronchoscopy after 2 months of the diagnosis. TO was confirmed with the histopathology of the biopsies from nodules. Then he was referred to an interventional pulmonologist for laser ablation.